Application Of Packaging And Labeling Technology For Oyster Mushroom Rendang In A Group of Women Farmers Cultivating Oyster Mushroom Limau Manis Sejahtera - Meutia Fiana, Risa; Koja, Reni; Febjislami, Shalati; Chairina, Dina; Kirana Ariani, Dwi (Andalasian International Journal of Social and Entrepreneurial Development, 2024)
The Limau Manis Sejahtera Farming Women's Group (KWT LMS) produces processed oyster mushroom products, namely oyster mushroom rendang, which is packaged using transparent plastic and simple labels. The packaging technique and design are still simple and not yet equipped with labels containing complete product information due to the lack of information KWT LMS members possess regarding product shelf life, technique, design and type of packaging. Increasing the knowledge possessed by KWT LMS members is necessary so that the processed mushroom products' packaging has good quality in maintaining the product's shelf life and attracting consumers' attention. The service activities include counselling regarding the importance of product packaging and labelling, providing assistance with packaging tools and practices, improving existing packaging designs, coaching in packaging aspects and further guidance regarding marketing. Extension activities and packaging practices affect increasing KWT LMS members' knowledge about the shelf life of products that have been produced and will be produced, packaging requirements, colour and packaging design requirements and techniques for choosing packaging from those who don't know (average score 1.24-1.29) to be quite knowledgeable (average score 1.24-3.43). The mushroom rendang packaging design with product information labels such as composition, expiry date, benefits, attractive visual appearance, and more suitable materials was also produced to improve the previously used packaging.